Diversity of springtails (Hexapoda) according to a altitudinal gradient - García-Gómez, Arturo; Castaño-Meneses, Gabriela; Palacios-Vargas, José Guadalupe (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to elevate gradient effect on diversity of Collembola, in a temperate forest on the northeast slope of Iztaccíhuatl Volcano, Mexico. Four expeditions were organized from November 2003 to August 2004, at four altitudes (2,753, 3,015, 3,250 and 3,687 m a.s.l.). In each site, air temperature, CO2 concentration, humidity, and terrain inclination were measured. The influence of abiotic factors on faunal composition was evaluated, at the four collecting sites, with canonical correspondence analyses (CCA). A total of 24,028 specimens were obtained, representing 12 families, 44 genera and 76 species. Mesaphorura phlorae, Proisotoma ca. tenella and Parisotoma ca. notabilis were the most abundant species. The highest diversity and evenness were recorded at 3,250 m (H' = 2.85; J' = 0.73). Canonical analyses axes 1 and 2 of the CCA explained 67.4% of the variance in species composition, with CO2 and altitude best explaining axis 1, while slope and humidity were better correlated to axis 2. The results showed that CO2 is an important factor to explain Collembola species assemblage, together with slope and humidity.